Public Policy Strategies for Reducing Informality in the Clothing Sector: Application of the Analytic Hierarchy Process - Castro, José Cícero de; Ferreira, Monaliza de Oliveira; Costa, Marconi Freitas da (Future Studies Research Journal: Trends and Strategies, 2019)
The goal of this study was to analyze public policies to encourage the reduction of informality in the Clothing Sector of Agreste Pernambucano, based on the multicriteria analysis method. Data from the analysis were collected through questionnaires with questions that compared the criteria (entrepreneurs with higher revenues, entrepreneurs with at least one employee and entrepreneurs involving the family in the business) and policy alternatives. Subsequently, the information collected for the application of the multi-criteria AHP (Analytic Hierarchy Process) method of decision support was used. Among the alternatives analyzed, such as the expansion of microcredit, tax reduction and increased inspection, this research has shown that the best policy to reduce informality in the Clothing Sector of Agreste Pernambucano is the expansion of microcredit.